2017
DOI: 10.15359/rca.52-1.2
|View full text |Cite
|
Sign up to set email alerts
|

Road Encroachment Near Protected Areas Alters the Natural Soundscape Through Traffic Noise Pollution in Costa Rica

Abstract: La invasión de caminos cerca de las áreas protegidas altera el paisaje natural sonoro debido a la contaminación del ruido por tránsito en Costa Rica Asistente:Sharon Rodríguez-Brenes Editorial:Editorial de la Universidad Nacional de Costa Rica (EUNA)Los artículos publicados se distribuye bajo una Licencia Creative Commons Atribución 4.0 Internacional (CC BY 4.0) basada en una obra en http://www. revistas.una.ac.cr/ambientales., lo que implica la posibilidad de que los lectores puedan de forma gratuita descarga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…For PAs in Aysén, and in other similar world regions where territorial transitions are being accelerated through new public works and infrastructure designed to provide better connectivity, access, and traffic flows, these types of participant ratings should raise important conservation concerns. Vehicles have been identified as one of the most problematic of the anthrophonic sound categories, as road encroachment in and around PAs has been shown to alter natural soundscapes and contribute to vehicular noise pollution (Mcdonald et al 2009;Francis et al 2017;Arévalo 2018;Buxton et al 2019). Gale et al (2018) identified increasing concern on the part of researchers and managers in Aysén who were worried about negative wildlife impacts associated with paving processes for the region's main roads that run adjacent or intersect several PAs.…”
Section: Discussionmentioning
confidence: 99%
“…For PAs in Aysén, and in other similar world regions where territorial transitions are being accelerated through new public works and infrastructure designed to provide better connectivity, access, and traffic flows, these types of participant ratings should raise important conservation concerns. Vehicles have been identified as one of the most problematic of the anthrophonic sound categories, as road encroachment in and around PAs has been shown to alter natural soundscapes and contribute to vehicular noise pollution (Mcdonald et al 2009;Francis et al 2017;Arévalo 2018;Buxton et al 2019). Gale et al (2018) identified increasing concern on the part of researchers and managers in Aysén who were worried about negative wildlife impacts associated with paving processes for the region's main roads that run adjacent or intersect several PAs.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic noise is a serious problem for many protected areas (Buxton et al., 2017; Francis et al., 2017), as it can have detrimental effects on natural soundscapes (Arévalo & Blau, 2018; Kaiser et al., 2011; Krause et al., 2011; Sun & Narins, 2005), biodiversity (Shannon, Angeloni, Wittemyer, Fristrup, & Crooks, 2014), and visitor experience (Iglesias-Merchan, Diaz-Balteiro, & Soliño, 2014; Manning, Newman, Fristrup, Stack, & Pilcher, 2010). Despite these adverse effects, there is a lack of legislation and monitoring of sounds levels and noise intrusion in protected areas (Arévalo & Blau, 2018; Burivalova et al., 2018; Krause et al., 2011, Shannon et al., 2016). The results of this study provide evidence of how PAZ can be implemented as a valuable strategy to minimize noise intrusion and how the type of zoning influences the soundscape composition and determines the amount and type of anthropogenic noises that occur.…”
Section: Discussionmentioning
confidence: 99%
“…For example, soundscape analysis can provide information about animal community composition (Aide, Herna´ndez-Serna, Campos-Cerqueira, Acevedo-Charry, & Deichmann, 2017;Campos-Cerqueira & Aide, 2017a;Farina & James, 2016;Krause & Farina, 2016) and its dynamics in urban areas (Fairbrass, Rennett, Williams, Titheridge, & Jones, 2017;Joo, Gage, & Kasten, 2011;Liu, Kang, Behm, & Luo, 2014) and natural areas (Burivalova et al, 2018;Krause, Gage, & Joo, 2011;Pekin, Jung, Villanueva-Rivera, Pijanowski, & Ahumada, 2012;Turner, Fischer, & Tzanopoulos, 2018;Tucker, Gage, Williamson, & Fuller, 2014). In addition, soundscapes have been used to evaluate the effects on fauna from high-noise levels associated with mining (Alvarez-Berr ıos et al, 2016;Duarte et al, 2015), natural gas exploitation , and vehicle traffic near protected areas (Are´valo & Blau, 2018;Munro, Williamson, & Fuller, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Roads and their traffic can affect wildlife over large areas and, in regions with dense road networks, may influence a high proportion of the ecological landscape (Cooke et al, 2020a). In Costa Rica, for example, 41.2 % of the protected areas are directly or indirectly influenced by the effect of roads, and 532.52 km of roads are adjacent to, or less than 2 km away from protected areas (Arévalo & Blau, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, bird movements, abundance, occurrence, and richness have been negatively correlated with road exposure (Reijnen et al, 1997;Laurance et al, 2004;Herrera-Montes & Aide, 2011;Cooke et al, 2020b). In Costa Rica, the number of biophonies (measured as the seconds occupied by bird vocalizations) was significantly lower near the road in Carara National Park (Arévalo & Blau, 2018). This difference was probably related to decreased bird density where road noise was highest (Arévalo & Newhard, 2011).…”
Section: Introductionmentioning
confidence: 99%